Método para avaliação e apoio à tomada de decisão em projetos para a geração de energia elétrica com biogás - Zank, João Carlos Christmann (2019)
The elaboration and diagnosis of technological arrangements for the generation of electric energy with biogas are complex and require a wide and multidisciplinary knowledge base. About the technical and economic arrangements that are inadequate for the local reality implies to an unsatisfactory result for investors and for the electric system as well as loss of prestige for a solution that has sometimes proved sustainable. An inadequately implemented project, in turn, generates negative impacts for the implementing, development and social institutions. In addition to the economic aspect, in which it may incur financial losses, such a mistaken implementation represents a waste of technical resources that jeopardize the sustainability of the institutions involved. The objective of this work is to present a method to support the diagnosis, analysis and decision making on technical and economic arrangements of projects for the generation of electric energy with biogas. The study has been carried out considering the analysis in 03 (three) Demonstration Units of electric energy generation with biogas already implanted in the West of the State of Paraná. To identify the factors that influence decision making in these projects, qualitative analysis methods were used, with the Ishikawa Diagram and SWOT matrix, which allow a participatory cause and effect analysis and a description of the internal and external factors influencing the project through the application of reduced SWOT. With the result of the analysis has been proposed a method that should aggregate the experience and lessons learned as guidelines to the diagnosis and elaboration of new arrangements. The reflections on the issues surrounding biogas to power projects, as well as the fact that it provides society with a tool for the evaluation and diagnosis of existing arrangements in a safe and fast way, popularizing and making feasible such solutions in a shorter term, is the advance towards the end of this research.